The Effect of Baby Massage on the Appetite of Wasted Toddlers at Manisrenggo Public Health Center, Klaten - Lusinta Agustina; Henik Istikhomah; Desti Reka Karena Sari (Universitas Malahayati Lampung, 2026)
ABSTRACT Wasting is a condition caused by inadequate nutritional intake or infectious diseases. This form of malnutrition can lead to changes in a child’s abilities, activity levels, and capacity to process various types of information. Baby massage is one alternative intervention that uses acupressure techniques by applying pressure to meridian points or energy flow lines on the body, which is relatively practical and easy to perform. This study aims to determine the effect of baby massage on the appetite of wasted toddlers at Manisrenggo Public Health Center, Klaten. This quantitative study used a quasi-experimental design with a one-group pretest–posttest approach. The research sample consisted of 30 wasted toddlers aged 12–60 months. The study was conducted in May 2024 using a purposive sampling technique. Baby massage treatment was administered for six consecutive days. Data were analyzed using the Wilcoxon test. The findings showed that the mean appetite score before baby massage was 3.5000, and after the intervention it decreased to 0.7000. Statistical analysis using the Wilcoxon test showed a p-value of 0.000, where p-value α (0.05), indicating that baby massage had a significant effect on the appetite of toddlers at Manisrenggo Public Health Center. The appetite of wasted toddlers improved after receiving baby massage, demonstrating a significant effect on appetite before and after the intervention. Keywords: Baby Massage, Appetite, Wasted Toddlers.